Digital Creativity - Sporton, G. author. aut Link
IX, 182 p.
Keywords: Examining the role and impact of technology on creative practice, and how technology evolution determines the forms and format of an artist's work, this book contextualizes technological revolutions with earlier encounters between craft and innovation, endorsing a notion of craft practice within computing that needs rescuing from tech industries.